Elevated Homocysteine Levels in Patients with Acute Ischemic Stroke (Medical Forum Monthly, 2020)
Objective: To determine the plasma homocysteine levels in patients with acute ischemic stroke at a tertiary care Hospital, Karachi.Study Design: A Cross Sectional study.Place and Duration of Study: This study was conducted at the Department of General Medicine, Liaquat National Hospital, Karachi from October 2019 to April 2020.Materials and Methods: All patients who fulfilled the inclusion criteria in the Department of General Medicine Liaquat National Hospital & Medical College, Karachi were included. After taking informed written consent history was taken, clinical examination was done and blood sample was sent for serum homocystein level to assess the outcome i.e. frequency of hyperhomocysteinemia.Results: Total of 191 patients of hyperhomocysteinemia with ischemic stroke was included. 120 patients (62.8%) were males & 71 patients (37.2%) were females with the mean age (years) was 51.2+11.4 years. Hyperhomocysteinemia was seen in 86(45%) patients.Conclusion: In conclusion hyperhomocysteinaemia, a modifiable risk factor for ischaemic stroke, was seen in about half of ischemic stroke patients, was predominant in male gender and common in patients with advance age.